(untitled) (Revista Electrónica REDINE, 2025)
The research analyzed the educational transformations that emerged during the COVID-19 crisis and their implications in the post-pandemic period, based on the theoretical perspectives of Dewey and Durkheim on the social function of education, within the framework of the Universal Declaration of Human Rights and Sustainable Development Goal 4 of the 2030 Agenda. Through a descriptive documentary research methodology, academic publications, institutional reports, and normative documents related to emerging pedagogical practices and the role of educational technologies during the pandemic were examined. The findings indicate that the abrupt transition towards hybrid teaching modalities, which impacted approximately 1.579 billion students in 191 countries, revealed notable digital disparities and deficiencies in teachers’ technological competencies. However, it also drove pedagogical innovations and the development of mixed teaching models. It is concluded that it is necessary to rethink traditional educational models towards more resilient systems that effectively integrate digital tools, strengthen teaching competencies, and ensure equitable access to quality education, especially in emergency contexts.